2013
DOI: 10.1158/0008-5472.can-12-4704
|View full text |Cite
|
Sign up to set email alerts
|

ALDH1-Positive Cancer Stem Cells Predict Engraftment of Primary Breast Tumors and Are Governed by a Common Stem Cell Program

Abstract: Cancer stem-like cells (CSC) have been widely studied, but their clinical relevance has yet to be established in breast cancer. Here, we report the establishment of primary breast tumor-derived xenografts (PDX) that encompass the main diversity of human breast cancer and retain the major clinicopathologic features of primary tumors. Successful engraftment was correlated with the presence of ALDH1-positive CSCs, which predicted prognosis in patients. The xenografts we developed showed a hierarchical cell organi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
89
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 47 publications
4
89
0
Order By: Relevance
“…Numerous studies concur that, in breast cancer and in cancers from other tissues, ALDH activity and/or expression identifies the subpopulation with highest tumorigenicity and metastatic potential [12,21,45,46]. General agreement also exists that ALDH1A1 correlates with ER– status in breast cancers and is an independent predictor of poor clinical outcome [12,22,27,45].…”
Section: Discussionmentioning
confidence: 97%
“…Numerous studies concur that, in breast cancer and in cancers from other tissues, ALDH activity and/or expression identifies the subpopulation with highest tumorigenicity and metastatic potential [12,21,45,46]. General agreement also exists that ALDH1A1 correlates with ER– status in breast cancers and is an independent predictor of poor clinical outcome [12,22,27,45].…”
Section: Discussionmentioning
confidence: 97%
“…Numerous preclinical studies have shown that expression of ALDH1 in tumor cells has been associated with stem-like characteristics, including innate chemoresistance and clonal capacity [17-20]. Moreover, expression of ALDH1 in surgically resected breast cancer is strongly associated with metastasis and poor survival [18,21].…”
Section: Introductionmentioning
confidence: 99%
“…It is now well established that cancer stem-like cells (CSCs) can be identified within in vivo tumor bulks or in vitro cell cultures thanks to several markers [1, 2, 3]. Many studies have already reported the presence of CSCs in different solid tumors, such as breast, brain, prostate, lung, ovary, colon, pancreas, liver, melanoma, head and neck [4, 5, 6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…This protein was first discovered on human hematopoietic stem cells and then identified in several cancers [4, 9]. Some studies also revealed that ALDH1, another common marker used for CSC identification, was also intimately correlated with tumorigenesis [1, 8, 15, 16]. …”
Section: Introductionmentioning
confidence: 99%